2016
DOI: 10.1007/s00192-016-3226-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of subsequent birth and delivery mode for women with previous OASIS: systematic review and meta-analysis

Abstract: Introduction and hypothesis Obstetric anal sphincter injuries (OASIS) are serious complications of vaginal birth. In a pregnancy following OASIS women may be keen to avoid an elective caesarean section, yet cautious about pursuing another vaginal birth that may result in further damage to the pelvic floor and possible long-term anal incontinence. This review aimed to evaluate the impact of subsequent birth and its mode on anal incontinence (AI) and/or quality of life (QoL), for women with previous OASIS. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 33 publications
0
14
1
2
Order By: Relevance
“…This present cohort study of consecutive women was also designed to investigate the impact of a subsequent birth by any [4][5][6][7][8][9]. Consequently, this study is of high methodological quality, which limits bias and satisfies the research recommendations highlighted in the published systematic review [3]. Repeat OASI rate in this study was 3.8%, lower than that found in other studies [17].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This present cohort study of consecutive women was also designed to investigate the impact of a subsequent birth by any [4][5][6][7][8][9]. Consequently, this study is of high methodological quality, which limits bias and satisfies the research recommendations highlighted in the published systematic review [3]. Repeat OASI rate in this study was 3.8%, lower than that found in other studies [17].…”
Section: Discussionmentioning
confidence: 81%
“…Since the introduction of the Royal College of Obstetricians and Gynaecologists (RCOG) Green-top Guideline "The Management of Third-and Fourth-Degree Perineal Tears in 2001" [2], the repair and immediate management of women who sustain OASIS has been standardised and improved. However, the recommendations on mode of birth for women who have a subsequent pregnancy are not based on good evidence from research specifically designed to investigate the effect of mode of subsequent birth on bowel function and quality of life in women with a previous OASI [3].…”
Section: Introductionmentioning
confidence: 99%
“…8,9,11,12 Moreover, a recent systematic review concluded that there is limited evidence on longterm quality of life among women who experience postpartum AI or undergo subsequent deliveries after sustaining OASIS. 13 Non-obstetric factors associated with an increased risk of long-term AI include adverse general health 14,15 and active bowel disease involving diarrhoea or constipation. [16][17][18] In addition, maternal age at first delivery is rising globally.…”
Section: Introductionmentioning
confidence: 99%
“…Women who have sustained OASIS at first birth and have a subsequent second pregnancy are exposed to the risk of a repeat OASIS that has been well quantified in the literature 2,3 , and to the potential risk of developing AI that is still to be determined with ongoing research 18 . Even if a repeat OASIS does not occur in the second childbirth, symptoms of AI might still present as a consequence of cumulative pudendal neuropathy, prolonged second labour or even an instrumental delivery at second birth 18 . On the other hand, there are recent reports that the risk of developing long term AI is not associated with the second delivery but only with the severity of OASIS at first childbirth 19 .…”
mentioning
confidence: 99%
“…In the case of long-term AI, there are additional factors that have been reported to aggravate the severity of bowel symptoms, such as age and menopause 17 . Women who have sustained OASIS at first birth and have a subsequent second pregnancy are exposed to the risk of a repeat OASIS that has been well quantified in the literature 2,3 , and to the potential risk of developing AI that is still to be determined with ongoing research 18 . Even if a repeat OASIS does not occur in the second childbirth, symptoms of AI might still present as a consequence of cumulative pudendal neuropathy, prolonged second labour or even an instrumental delivery at second birth 18 .…”
mentioning
confidence: 99%